Pendekatan Total Quality Management terhadap Insentif, dan Kualitas Produk dalam Mengarahkan Keputusan yang Tepat - Ananto Krisna Wardhana; Kurniawan Prambudi Utomo; Riris Lestiowati; Rachmat Fadly (Jurnal Kajian Ilmiah, 2024)
This research aims to approach the relationship between the application of Total Quality Management (TQM) on incentives and product quality on making appropriate management decisions. This study uses quantitative and qualitative methods through data analysis from several organizations that implement TQM and have a structured incentive system and conduct field observations (field research) using the self-administered questionnaires method, namely distributing questionnaires directly face to face to these respondents using The population was taken from 155 respondents in a saturated sample and carried out in September-December 2023 using data analysis using multiple linear regression analysis and distributing questionnaires and interviews as well as literature studies, after which data processing was carried out using SPSS version 26 statistical data processing analysis. The research results show that the implementation of TQM consistently improves product quality significantly. Well-designed incentives, which support innovation and collaboration, strengthen the positive effects of TQM on employee performance. In addition, product quality has been proven to influence management decision making appropriately, encouraging more strategic and long-term oriented decisions. The integration of TQM practices and appropriate incentive systems has a positive impact on the organization's adaptability and responsiveness to market changes and achieving sustainable competitive advantage.